2021
DOI: 10.26418/jeltim.v3i1.41696
|View full text |Cite
|
Sign up to set email alerts
|

DEVELOPING HoPALM AS TEACHING MATERIALS FOR SECONDARY HIGH SCHOOL STUDENTS

Abstract: This research was aimed to develop a product named HoPALM, hot-potatoes assisted listening material for secondary high school students. This research applied development research and ADDIE procedure. In the analysis stage, the researcher found the fundamental problems and needs of the students as well as the opportunity as the background of developing HoPALM. In the designing and developing stage, the researcher collected the sources that needed and develop HoPALM by using the features available on the hot-pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…As the gap of this research, the researcher designed supplementary materials of procedure text for senior high school and focus on writing skills. Furthermore, related to the media showing the materials, two previous studies who used multimedia-based to design the materials, were Sauramanda et al, 2022, andUtami et al, 2022. These studies showed the importance of media used in displaying the materials.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As the gap of this research, the researcher designed supplementary materials of procedure text for senior high school and focus on writing skills. Furthermore, related to the media showing the materials, two previous studies who used multimedia-based to design the materials, were Sauramanda et al, 2022, andUtami et al, 2022. These studies showed the importance of media used in displaying the materials.…”
Section: Introductionmentioning
confidence: 97%
“…These studies showed the importance of media used in displaying the materials. Sauramanda et al, 2022 developed supplementary material using Ispring Quizmaker, while Utami et al, 2022 developed supplementary materials using Hot Potato. Their studies supported the researchers' decision to carry out this study.…”
Section: Introductionmentioning
confidence: 99%